The - Shelton, Richard (University of Pittsburgh Press, 2007)
While Shelton has been known primarily for his poems dealing with the landscape of the Southwest and the destruction of that landscape, the poems in this book are much more far-ranging, including many poems dealing with soocial issues (the issue of illegal immigration on our southern border, homelessness), historical events (the war in Iraq, the events of 9/11) and attitudes concerning politics and the environment. The poems are filled with sensory images, engaged in the real world, often ironic or simply off-the-wall, and their tone ranges from deeply sad, as in a requiem for Glen Canyon on the Colorado River, to the wildly funny, as in Brief Communications from My widowed Mother